PENINGKATAN KETERAMPILAN BERBICARA SISWA DENGAN METODE BERMAIN PERAN (ROLE PLAY) DI KELAS VII B SMP NEGERI 2 SAROLANGUN - Elmiati S.Pd; Yahfenel Evi Fussalam (STKIP Muhammadiyah Muara Bungo, 2018)
This study investigated students’ speaking skill and the factors were influenced the changes of students’ speaking skill at grade VII B SMP N 2 Sarolangun. The researcher analyzed students’ speaking included content, grammar, fluency, pronunciation, and vocabulary which categorized into poor, average, good, and very good. The method of this research was descriptive quantitative. The data of this research were collected by using observation, speaking test and interview The data were analyzed by using quantitative and qualitative data analysis. The finding showed that (1) generally, the students’ KKM were increased; 7 students’ (23,3%) in pre-cycle test increased slightly into 12 students (40%) in first cycle, and significantly 23 students (76,7%) in second cycle, (2) the changes of students` speaking skill were influenced by two factors, namely, (a) internal factor that the students` speaking skill such as motivation and anxiety, and (b) external factors that affected of teaching materials. This study indicated that the students’ speaking skill can be improved by using role playing method.